Absorption of nicotine and carbon monoxide from passive smoking under natural conditions of exposure. Issue 11 (November 1983) - Jarvis, M J; Russell, M A; Feyerabend, C
Abstract : Seven non-smokers were exposed to tobacco smoke under natural conditions for two hours in a public house. Measures of nicotine and cotinine in plasma, saliva, and urine and expired air carbon monoxide all showed reliable increases. The concentrations of carbon monoxide and nicotine after exposure averaged 15.7% and 7.5% respectively of the values found in heavy smokers. Although the increase in expired air carbon monoxide of 5.9 ppm was similar to increases in smokers after a single cigarette, the amount of nicotine absorbed was between a tenth and a third of the amount taken in from one cigarette. Since this represented a relatively extreme acute natural exposure, any health risks of passive smoking probably depend less on quantitative factors than on qualitative differences between sidestream and mainstream smoke.